PROMOTION STRATEGY AND WORD OF MOUTH ON PURCHASE DECISIONS WITH BRAND AWARENESS AS A MODERATING VARIABLE ON BEZZIE MINI SOCCER - Al Hilal Akbar Ferdynanda; Endang Sulistya Rini; Syahyunan (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the influence of promotional strategies and word of mouth on purchase decisions, with brand awareness as a moderating variable at Bezzie Mini Soccer. Competition in the sports industry, particularly in mini soccer field rentals, is becoming increasingly intense, requiring effective marketing strategies to sustain and enhance consumer purchasing decisions. The research adopts a quantitative approach through a survey method involving 85 respondents who have previously used Bezzie Mini Soccer's services. The data analysis technique employed is Structural Equation Modeling – Partial Least Square (SEM-PLS). The results indicate that both promotional strategies and word of mouth have a positive and significant effect on purchase decisions. Brand awareness also significantly influences purchase decisions and moderates the relationship between promotional strategies and word of mouth with purchase decisions. These findings highlight the importance of consistent promotion, positive recommendations, and strong brand awareness in shaping consumer purchasing behavior.